Cross-border banking, bank market structures and market power: Theory and cross-country evidence - Bremus, Franziska M. (Journal of Banking & Finance, 2015)
Patterns in cross-border banking have changed since the global financial crisis. This may affect domestic bank market structures and macroeconomic stability in the longer term. In this study, I theoretically and empirically analyze how different modes of cross-border banking impact bank concentration and market power. I use a two-country general equilibrium model with heterogeneous banks developed by DeBlas and Russ (2010a) to grasp the effect of cross-border lending and foreign direct investment in the banking sector on bank market structures. The model suggests that both cross-border lending and bank FDI mitigate concentration. Empirical evidence from a panel dataset of 18 OECD countries supports the theoretical predictions: higher volumes of bank FDI and of cross-border lending coincide with lower Herfindahl-indexes in bank credit markets.